PENGEMBANGAN LKPD BERBASIS CREATIVE PROBLEM SOLVING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA MATERI SEGI EMPAT DAN SEGITIGA - Anggraini, Ahda Zuliana; Muniri, Muniri; Zahroh, Umy (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
The purpose of this research to produce Creative Problem Solving (CPS)-based LKPD that meet the criteria of validity, practicality and effectiveness to improve critical thinking skills in quadrilateral and triangle material. The research type is Research and Development (R&D) ADDIE model which Analysis, Design, Development, Implementation and Evaluation. Data collection techniques use observation, interviews, questionnaires and tests. The product test subjects were class VIII students at SMP Negeri 1 Patianrowo and SMP Negeri 2 Patianrowo. The results of the research according to expert assessment show that the teaching materials developed have valid criteria. This means that the teaching materials developed are suitable for use by students. The assessment based on the results of teacher and student response tests shows that the teaching materials developed meet the criteria of being very practical. This means that the teaching materials developed can be implemented in the mathematics learning process, especially in quadrilaterals and triangles. The posttest results show that there is a significant difference in critical thinking abilities between the control class and the experimental class. This means that the teaching materials developed have an effect on increasing students' critical thinking skills with the percentage of increase being at a very high effect, namely 80.2%. Based on this assessment, it can be concluded that the teaching materials developed have met the criteria for validity, practicality and effectiveness in improving critical thinking skills of student in quadrilateral and triangular material